En sociologtidskrift på svenska - varför då? (Sociologisk Forskning, 2000)
Why a Swedish journal of sociology?The article discusses the problems of the journal “Sociologisk forskning”, such as low scientific impact, and proposes a change of publishing policy in order to change the journal into a policy-oriented forum.